Women empowerment in urban governance in India - Prasad, D. Ravindra (2014)
In an urbanising world women constituting half the population have a very limited role in urban governance-policy and decision-making as they are not adequately and appropriately represented in the urban local bodies. The 74th Constitution Amendment Act, 1992 for the first time provided one-third representation to women in urban local self-government institutions. This has raised the question as to what key role they could play in urban governance. This article examines the role of women mayors, chairpersons and councillors in city's development and local governance. It argues that there is no difference between men and women mayors, chairpersons and councillors as regards their formal roles. There are areas, however, where women can play a catalytic role in promoting the causes of social development including women and child development. The number of women in the council though critical is not sufficient enough to neither impact the policies and decisions nor empower women. It requires capacity enhancement to build awareness, training, sharpening their skills, motivation and building confidence, and to engage in general and gender-based urban governance issues. - Reproduced.
Keywords: Urban development - India; Women - India; Women